Enhancing Agro Packaging Textiles : Innovations and Functional Formulations for Improved Agricultural Productivity and Sustainability - Sharan Shetty (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
One third of the Agro production is lost due to improper handling, storage and microbial contamination as well as environmental effects. The Agricultural sector has crucial contribution to the Nation’s economy so it is imperative to take proactive steps to minimize the losses and functional formulations in finishing or as additives can prove as an active game changer in the Agro Packaging Industry. By using essential oil and functional formulations consisting of Anti-microbial, UV repellent and Anti-rodent properties would be the most effective for the Agro-packaging because of being susceptible to such environment.
Keywords: Additives; Agro Packaging; Functional Formulations; Finishing